A Healthcare Center intergrated with Community and Nature - CHEN, JINFENG; LIU, DANNA (My University, 2023)
Concept Our concept is that we want to build a a Healthcare Center intergrated with Community and Nature . Boundary Our site is located at the boundaries of the new town and the old town .The old town ends here, but the new town is not fully established. Our buildings should be some kind of link between the old and new cities. Heritage Vadstena is a city with cultural heritage and beautiful scenery. Many people will come there in their spare time and even move for retirement.Our architecture is in this sequence. In future construction, our buildings should become part of this sequence of heritage and help it grows. Comunity The location of our site was used to be a healthcare community. In some way ,it was more like a open healthcare community than a closed hospital.Our design aims to build a new healthcare center as a small open community towards the whole town. Nature and Sustainability We want this new healthcare center to be sustainable. We maximize the use of building space and sustainable materials. At the same time, solar energy, wind energy, rainwater recycling and other technologies are used to build a green building with low energy consumption.